2014
DOI: 10.1088/0964-1726/24/2/025002
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and optimization of a novel two-axis mirror-scanning mechanism driven by piezoelectric actuators

Abstract: Mirror-scanning mechanisms are a key component in optical systems for diverse applications. However, the applications of existing piezoelectric scanners are limited due to their small angular travels. To overcome this problem, a novel two-axis mirror-scanning mechanism, which consists of a two-axis tip-tilt flexure mechanism and a set of piezoelectric actuators, is proposed in this paper. The focus of this research is on the design, theoretical modeling, and optimization of the piezoelectric-driven mechanism, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Therefore, the gravity effect of the mirrors during the analysis can be ignored to simplify theoretical calculations and simulations. Table 4 compares the static performance of Devices A and B presented in this paper with other piezoelectric scanning mirrors reported in the literature [ 11 , 21 , 42 , 43 , 44 ]. It is demonstrated that the proposed devices tend to exhibit an outstanding θ · D product.…”
Section: Three-dimensional (3d) Finite-element Modeling (Fem) Simulation Optimization and Discussionmentioning
confidence: 99%
“…Therefore, the gravity effect of the mirrors during the analysis can be ignored to simplify theoretical calculations and simulations. Table 4 compares the static performance of Devices A and B presented in this paper with other piezoelectric scanning mirrors reported in the literature [ 11 , 21 , 42 , 43 , 44 ]. It is demonstrated that the proposed devices tend to exhibit an outstanding θ · D product.…”
Section: Three-dimensional (3d) Finite-element Modeling (Fem) Simulation Optimization and Discussionmentioning
confidence: 99%
“…To protect the piezoelectric stack and ensure its expansion amplitude during use, it is necessary to design a clamping and fixing structure for the piezoelectric stack [14,15]. Preloading of the piezoelectric stack is necessary to prevent the piezoelectric stack from escaping from the structure.…”
Section: Design Of Piezoelectric Compensation Structurementioning
confidence: 99%
“…All in all, the PAMs based on PZT stack actuators aligned in parallel and flexible hinge magnifying mechanisms by directing driving method can achieve high resolution and fast response, but they generally cannot reach the range of millimeter level or degree level due to the short stroke of PZT stack [25][26][27], and the decoupling characteristic and the cost are usually contradictory (reducing the mechanical coupling by increasing the number of actuators). In addition, the structure with flexible hinge mechanism usually reduces the stiffness of PAMs [28][29][30].…”
Section: Introductionmentioning
confidence: 99%